Energy transfer process in the reaction system NH2OH-OH-NaOH-CU(II)−Eu(III) / thenoyltrifluoroacetone - Stefan Lis; Małgorzata Kaczmarek (International Journal of Photoenergy)
Chemiluminescence (CL) in the system containing hyrdroxylamine, sodium hydroxide, copper(II) ions and complex of europium(III) with thenoyltrifluoroacetone has been studied. A weak emission arises from hydroxylamine in the presence of copper(II) ions in a basic aqueous solution. Addition of europium(III) chelate to this system causes a significant increase in the chemiluminescence intensity. The dominant band observed in the emission spectrum occurs at λ∼ 600 nm, confirming that Eu(III) ions are the only emitters in the system studied. A strong correlation between the CL intensity and the concentrations of europium(III) chelate was observed. It means that europium(III) thenoyltrifluoroacetone complex does not influence the oxidation rate of hydroxylamine and indicates its important role in this reaction as a sensitiser. A possible mechanism of the chemiluminescence of the NH2OH-OH-NaOH-CU(II)−Eu(III) chelate system is presented.